2020
DOI: 10.34172/joddd.2020.042
|View full text |Cite
|
Sign up to set email alerts
|

In vitro testing of shear bond strength of orthodontic brackets bonded to different novel CAD/CAM ceramics

Abstract: Background. The present study aimed to evaluate the bond strength of metal bracket (MB) and ceramic bracket (CB) bonded to different CAD/CAM ceramic substrates etched with hydrofluoric acid (HFA) vs. phosphoric acid (PA). Methods. A total of 120 CAD/CAM ceramic blocks in 12 groups were fabricated from three different CAD/CAM ceramic materials: VITABLOCS Mark II, VITAENAMIC, and IPS e.max CAD. Each ceramic material group was divided into two etching groups: one treated with 9.5% HFA and the other treated with 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…(1) Phosphoric Acid 37%, Silane, and Bonding . The metasample of the included two studies [ 23 , 24 ] was homogenous ( I 2 = 0.0%, P = 0.734). Both studies similarly showed effect sizes close to the gold standard.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…(1) Phosphoric Acid 37%, Silane, and Bonding . The metasample of the included two studies [ 23 , 24 ] was homogenous ( I 2 = 0.0%, P = 0.734). Both studies similarly showed effect sizes close to the gold standard.…”
Section: Resultsmentioning
confidence: 99%
“…(1) Metal Brackets: Phosphoric Acid 37%, Silane, and Bonding . This meta-analysis included three studies [ 23 , 24 , 28 ]. There heterogeneity was significant ( I 2 = 73.8%, P = 0.018).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations